Anti-SARS-CoV-2 spike IgG following injection of the third dose vaccine: A systematic review with meta-analysis of heterologous versus homologous vaccination - Mojadadi, Mohammad-Shafi; Javadinia, Seyed Alireza; Attarian, Fahimeh; Samami, Elham; Sobhani, Mona (Frontiers in Public Health, 2023)
Background: The mass vaccination is the main strategy in controlling and managing the COVID-19 pandemic. Today, several vaccines using different platforms have been developed against SARS-CoV-2 around the world. These vaccines are usually administered in a two-dose schedule, and the third dose is currently being injected in most countries. In this study, the immunogenicity of heterologous versus homologous vaccination after injection of the third dose of COVID-19 vaccines has been reviewed and analyzed. Methods: This is a systematic review and meta-analysis to assess the immunogenicity of the third dose of COVID-19 vaccines on 2808 healthy individuals (age ≥18 years) with mean age 57.1 years based on available data in randomized clinical trials studies published within the last two years. The concentrations of anti-spike and anti-receptor binding domain (RBD) antibodies 28 days after receiving the third dose for five homologous and 18 heterologous types of vaccines were extracted for comparing immunogenicity between vaccination regimens. All data were analyzed using STATA 16. Results: The highest antibody responses had been reported for the homologous vaccination regimen of m1273 (Moderna), followed by the heterologous regimen of BNT/BNT/m1273. In addition, the immunogenicity of viral vector and inactivated vaccines was remarkably enhanced when they had been administered in a heterologous regimen, especially with a third dose of mRNA vaccines. Conclusion: This systematic review suggests that mRNA vaccines in a homologous regimen induce strong antibody responses to SARS-CoV-2 compared to other vaccine platforms. In contrast, viral vector and inactivated vaccine platforms show a satisfactory immunogenicity in a heterologous regimen, especially in combination with mRNA vaccines. Keywords: SARS-CoV-2, COVID-19 vaccine third dose, Heterologous vaccination, Homologous vaccination, Anti-SARS-CoV-2 antibody